Ki-67 Proliferation Index in Renal Biopsy Samples of Patients With Systemic Lupus Erythematosus and Its Correlation with Clinical Findings (Iranian Journal of Kidney Diseases, 2013)
Introduction. Systemic lupus erythematosus is an autoimmune disease that may affect almost all organ systems. Renal involvement is the most significant prognostic factor. Renal biopsy findings play an important role in treatment decision. Ki-67 is a monoclonal antibody that is only found in proliferative cells. This study aimed to investigate the proliferative activity in renal biopsy specimens of patients with lupus nephritis using the Ki-67 monoclonal antibody, and to compare the proliferative index between different subgroups of patients. Materials and Methods. Renal biopsy specimens of 29 patients with systemic lupus erythematosus were retrospectively evaluated. Type of lupus nephritis and activity and chronicity indexes were determined. Ki-67 immunostaining was performed. For each patient, 1000 cells were counted and the number of Ki-67 positive cells was determined. The Ki-67 activity index was compared between different subgroups of lupus nephritis and correlated with systemic lupus erythematosus disease activity index, serum creatinine, proteinuria, anticardiolipin antibodies, and complement levels. Results. A positive correlation between Ki-67 proliferation index, serum creatinine levels, and systemic lupus erythematosus disease activity index were found. Although conventional activity indexes were low, in 3 of 9 patients with class II lupus nephritis, Ki-67 proliferation indexes were high, indicating proliferation. Conclusions. Ki-67 can be used as a proliferation marker in renal biopsy specimens for patients diagnosed with systemic lupus erythematosus.